Pregnancy Complicated by Portal Hypertension Secondary to Biliary Atresia - O. E. O'Sullivan; D. Crosby; B. Byrne; C. Regan (Hindawi Limited, 2013)
Biliary atresia is a rare idiopathic neonatal cholestatic disease characterized by the destruction of both the intra- and extrahepatic biliary ducts. As the disease is progressive all cases will develop portal fibrosis, cirrhosis, and portal hypertension with the sequelae of varices, jaundice, and eventually liver failure requiring a transplant. Survival rates have improved considerably with many females living well in to be childbearing age. Due to the complexity of the disease these pregnancies are considered, high risk. We report the antenatal, intrapartum, and postpartum managements of a pregnancy complicated by biliary atresia. Furthermore, we highlight the importance of a multidisciplinary team approach in optimizing obstetric care for this high risk group.